FASHION BUSANA HAJI DI DESA TOPEJAWA KABUPATEN TAKALAR (ANALISIS MAKNA SONGKO’ AJJI WANITA) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This study discusses the Fashion of Women's Hajj Clothing in Topejawa Village, Takalar Regency. The main problem in this study is how the meaning of Songko' Ajji Women as Hajj Clothing Fashion in Topejawa Village, Takalar Regency, and whether the compatibility between the tradition of wearing Songko' Ajji Women in Topejawa Village, Takalar Regency in accordance with Islamic law or not. This study uses a qualitative research type with the approach used is a phenomenological approach. In this study, researchers used data collection methods, namely observation, interviews, and documentation. The data processing and analysis technique went through four stages, namely data reduction, data display, comparative analysis, and drawing conclusions. The results of this study indicate that the female Songko' Ajji who is often named by female pilgrims in Topejawa Village is shaped like the male Songko' Ajji where the shape is circular following the shape of the head using a rubber back for size adjustment without adhesive. Made of cloth sewn with gold thread or other floral motifs wrapped around it. The thread made of gold or in the Makassar language "Bannang Bulaeng" and coiled around Songko' Ajji means that the more circles of gold thread found in Songko' Ajji, the higher the degree of the wearer. Meanwhile, the male Songko 'Ajji is in a circular shape following the head without using the rubber on the back. The meaning of the songko 'Ajji woman in Topejawa Village, Takalar Regency is a symbol attached to the community order that the person has made the pilgrimage. Related to history, Songko 'Ajji this woman is the difference between people who have made the pilgrimage and those who have not. Those who have made the pilgrimage can use the woman's Songko 'Ajji, while those who have not made the pilgrimage may not use it. But there are some people who use female Songko 'Ajji even though they have not set foot in the holy land. They assume that the woman's songko 'ajji is not only intended for people who have made the pilgrimage but is used as a head covering. In the Islamic view, the use of Songko' Ajji by women in the community structure in Topejawa Village, Takalar Regency is not in accordance with Islamic law because in the use of Songko' Ajji the woman does not cover her nakedness completely but only as a head covering or only as a symbol.